Updates on First-Line Therapy for Metastatic Pancreatic Adenocarcinoma - Marks, Eric; Saif, Muhammad Wasif; Jia, Yuxia (JOP. Journal of the Pancreas, 2014)
Pancreatic adenocarcinoma is the 10th most common malignancy in the United States but is responsible for the 4th most cancer related deaths. This disease can only be potentially cured through early discovery and complete surgical resection. Unfortunately, nearly half of patients have metastatic spread at presentation. Combination chemotherapy with FOLFIRINOX or gemcitabine with nab-paclitaxel can prolong survival in selected patients, but at the cost of significant toxicity. In the 2014 ASCO Gastrointestinal Cancers Symposium, several studies were presented that focus on the management of metastatic pancreatic cancer. A phase II trial by Le et al. (Abstract #177) found that the addition of CRS-207, a strain of Listeria modified to stimulate an anti-tumor immune response, improves survival in patients being treated with GVAX. Goldstein et al. (Abstract #178) presented a post-hoc survival analysis for the phase III MPACT trial that shows the addition of nab-paclitaxel to gemcitabine produces a persistent survival benefit. Ramanathan et al. (Abstract #224) demonstrated that, with appropriate dose adjustments and delays, induction nab-paclitaxel and gemcitabine followed by mFOLFIRINOX consolidation is a feasible treatment option for metastatic pancreatic cancer. Despite these advances, it is imperative that we continue to work towards developing additional treatment options that are better tolerated and further prolong survival for these patients. This highlight article focuses on the first-line therapy of metastatic pancreatic adenocarcinoma. Image: Penn State Hershey Medical Center. Hershey, PA, USA